Histomorphometric analyses of area fraction of different ratios of Bio‐Oss® and bone prior to grafting procedures – An in vitro study to demonstrate a baseline. Issue 2 (27th October 2017) - Aludden, Hanna; Dahlin, Anna; Starch‐Jensen, Thomas; Dahlin, Christer; Mordenfeld, Arne
Abstract: Objective: The objective of this study was to estimate the area fraction of different ratios of Bio‐Oss ® and bone, prior to grafting in an in vitro model to demonstrate a histomorphometric baseline. Methods: Bio‐Oss ® particles were mixed with autogenous bone from pig jaw in three different ratios (50:50, 80:20 and 100:0) and packed in rice paper in a standardized procedure. Histomorphometric analyses were performed in 25 specimens and 74 regions of interest. The area percentage of Bio‐Oss ®, bone, and non‐mineralized tissue (NMT) were calculated. Results were reported as mean values and 95% confidence interval (CI). Results: The mean area fraction of Bio‐Oss ® was 20.6% (CI: 18.2–23) in the 50:50 mixture, 33.6% (CI: 29.7–37.6) in the 80:20 mixture, and 43.4% (CI: 40.5–46.3) in the 100:0 mixture. The mean area fraction of NMT was 60.5% (CI: 57.9–63.1) in the 50:50 mixture, 59.6% (CI: 56.4–62.7) in the 80:20 mixture, and 56.6% (CI: 53.7–59.5) in the 100:0 mixture. The mean area fraction of bone was 18.9% (CI: 16.9–20.9) in the 50:50 mixture and 6.8% (CI: 5–8.6) in the 80:20 mixture. Conclusion: There is a great difference in the clinically estimated percentage and the histomorphometrically evaluated percentage of Bio‐Oss ® at baseline, prior to grafting. The area fraction of different tissues presented in this study may be beneficial as guidance for histomorphometrical baseline calculations when different mixtures of Bio‐Oss ® and autogenous bone are used as grafting materials.